Implementasi Program Sekolah Ramah Anak di Sekolah Dasar Negeri Kecamatan Marpoyan Damai Kota Pekanbaru - Yuyun Yuyun; Zarkasih Zarkasih; Amalia Sapriati (Jurnal Bidang Pendidikan Dasar, 2022)
This study aims to evaluate the child-friendly school program (SRA) in Public Elementary Schools in Pekanbaru. Evaluation research in this study uses a discrepancy model of evaluation. The population of this study were all teachers and education personnel at SDN Marpoyan Damai District, Pekanbaru City who carried out the SRA program as many as 6 schools. The sampling technique in this research uses total sampling. Data analysis in this study used descriptive statistics. The results of the analysis show that the evaluation of SRA program policies, teaching and learning processes, readiness of educators and education staff in implementing, facilities and infrastructure used, student participation, participation of parents, community institutions, the business world, and alumni in the success